Otimização de produção, purificação e caracterização parcial de lipases produzidas pela levedura Moniliella spathulata R25L270 - Felipe Tadeu Fiorini Gomide (2012)
In this work, the main variables and their levels that influence the production of lipase(s) of Moniliella spathulata R25L270 were studied, in addition to the chromatographic purification of these enzyme(s) and characterization of the fractions collected. Thus, it was executed a mixed level factorial design L18, followed by two full factorial designs (23+1) of a culture medium containing 0.1% peptone, 0.02% of NaNO3 and one of two carbon sources (glycerol or olive oil). It was realized that, for glycerol as a source of carbon, the variables [C], pH and PO4 provided the best conditions for enzyme production in concentrations of 9.0%, 6.5 and 0.1%, respectivelly. For the optimization with the olive oil it was found the best condition in concentrations of 6.5 and 0.1% of the variables pH and PO4 respectivelly. It was also noted that the carbon sources would modify the production of enzymes. The best condition of purification was reached using ammonium sulphate precipitation, ultrafiltration in Amicon® systems and and gel filtration chromatography that allowed the isolation of two activity pools, each in a distinct fraction of saturation ammonium sulfate. The fractions obtained from the extracts of 60 and 80% of saturation obtained maximum activities for different alkyl esters of fatty acids, cations, pH and temperature, a strong indication of the production of at least two different lipases by Moniliella spathulata R25L270.